Podčrtna opomba k Aristotelovi definiciji metafore - Koren, Evald (Primerjalna književnost, 2010)
After demonstrating the inadequacy of translations of terms for metaphor in the Slovenian editions of Aristotle's Poetics, this paper focuses on the extent to which the traditional translations of Aristotle's definitions of metaphor into Slovene and other European languages are adequate and convincing.
Keywords: Aristoteles, 384-322 pr.n.š.; retorika; rhetoric; Aristotel: Poetika; metafora; metaphor; epifora; prevajanje; translation